Understanding peoples' participation in urban local government in West Bengal. Issue 1 (2nd January 2020) - Das, Maumita; Chattopadhyay, Soumyadip
ABSTRACT: In light of the potential of the 74th Constitutional Amendment Act to reinforce participatory practices in Indian cities, this paper, based on field observation from two municipalities of West Bengal, examines the nature of peoples' participation and identifies the socio-economic factors determining effective participation. It finds that in West Bengal, municipalities' failures to set up ward committees, the highly partisan nature of the ward committee, and non-occurrence of ward committee meetings made the general population disinterested in utilising these available democratic forum. Elected representatives became the only link between citizens and the municipal administration, and their representation did not necessarily result in effective participation.